Analysis of Banana Leaves as Noise Reducing Media With Addition of Zalacca Plam Peel - Irmadona Irmadona; Elwy Asrianto Marbun; Aisyah Nurul Ilmi Lubis; Putri Lynna A. Luthan (Universitas Negeri Medan, 2019)
At present there are very many sound absorbers developed with modifications from various simple materials available. A comparative study and analysis of banana midribs as a sound dampening medium has been tested by several other researchers, but not with the addition of zalacca bark. This research was continued to find out whether salak skin would reduce the sound. In this study carried out by the method of making banana midrib fiber, salak skin carbonization, composite fabrication and specimen testing. The specimens used is 30x30 cm. This composite consists of polyester resin as a matrix, banana midrib fiber and salak skin as a pore enhancer with a ratio of 5: 1. The results of the data from this analysis are that the sound can be muted by a composite that has been tested with a specimen test of 6 dB; 8.3 dB; 16.8 dB; 16.9 dB; 14 dB.